2006
DOI: 10.1121/1.2190165
|View full text |Cite
|
Sign up to set email alerts
|

Sound absorption by viscoelastic coatings with periodically distributed cavities

Abstract: Thin rubber layers with air-filled cavities can be used as anechoic submarine coatings. Normally incident sonar energy is redistributed in the lateral direction and absorbed. In this paper, the anechoic effect is studied theoretically and numerically by adapting techniques used in electron scattering and band-gap computations for photonic and phononic crystals. Reflection and transmission matrices are computed recursively, from basic ones for layers containing periodic arrays of spherical cavities. A method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(54 citation statements)
references
References 16 publications
0
53
0
1
Order By: Relevance
“…Calculating the transmission and reflection coe cients for an incident longitudinal wave on such a structure is a complicated matter. Indeed, the coupling between the cavities is too strong to be neglected, and shear waves also need to be taken into account, two factors that make numerical simulations computationally intensive [20,21]. However, a simple model was recently proposed [22] to calculate the transmission and reflection from a single layer of bubbles.…”
mentioning
confidence: 99%
“…Calculating the transmission and reflection coe cients for an incident longitudinal wave on such a structure is a complicated matter. Indeed, the coupling between the cavities is too strong to be neglected, and shear waves also need to be taken into account, two factors that make numerical simulations computationally intensive [20,21]. However, a simple model was recently proposed [22] to calculate the transmission and reflection from a single layer of bubbles.…”
mentioning
confidence: 99%
“…In LRSMs, locally resonant absorption coincides with viscoelastic deformation [11][12][13][14][15][16][17][18]. The sound-absorption region in LRPCs was first found using the multiple-scattering approach; these results showed that a conversion from longitudinal mode to transverse mode near the locally resonant frequencies effectively enhanced the anechoic performance of these materials [7,14].…”
Section: Introductionmentioning
confidence: 96%
“…As detailed in [17], for example, and references therein, reflection and transmission matrices R B ,T B and R A ,T A can now be introduced, for the discrete set of waves specified by (1)-(3). The mentioned reference concerns the doubly periodic case for a 3D PC, with periodicity in the y direction as well, but the R/T matrix formalism is the same.…”
Section: Basic 2d Layer Multiple-scattering Computational Methodsmentioning
confidence: 99%
“…Moroz [21] has published a representation of lattice sums in terms of exponentially convergent series, which has been used in the present work for numerical evaluation of the Θ quantities defined in (17).…”
Section: Computation Of the Expansion Coefficientsmentioning
confidence: 99%